HBR guide to better mental health at work (Boston, Massachusetts : Harvard Business Review Press, 2022)
'Though the pandemic increased the visibility of our whole selves, making virtual vulnerability a more regular workplace occurrence, stigma surrounding mental illness remains. It's easy to ask for time off when you break a leg; it's difficult to share with your boss and colleagues if you're suffering a depressive episode. And, how do those conversations go if you're the boss? You want to say and do the right thing to support your people and your organization-and avoid legal issues. Research shows that 1 in 4 adults will have a mental health issue in their lifetime, and yet we're still ill-equipped at work to address this common experience. The HBR Guide to Better Mental Health at Work collects advice from a variety of experts on addressing an array of mental health issues in the workplace, from supporting someone in a panic attack to navigating sensitive conversations to creating systemic and structural supports for all employees. Whether you suffer from a chronic condition or you manage someone who does, you'll find practical advice on creating and upholding policies; providing resources, support, and accommodations; and steps you can take to reduce the stigma and improve mental health in the workplace. You'll learn how to: talk about mental health at work, make a disclosure, take a disability leave, cope more effectively with feelings of anxiety and depression, manage a chronic condition and your career-successfully, give support without overstepping, create a more empathetic culture, launch an employee resource group to provide support and connection'--
Introduction: Our Mental Health at Work : we can no longer pretend everything is fine / by Morra Aarons-Mele -- Section 1. Having Conversations About Mental Health: Talking About Your Mental Health at Work : tips on asking for what you need / by Kelly Greenwood -- Discussing Your Mental Health with Your Boss : opening up can make us happier and more productive / by Deborah Grayson Riegel - Section 2. Caring for Your Mental Health: Structuring the Workday to Support Your Mental Health : build routines and unfocused time into your schedule / by Alice Boyes -- Managing Your Anxiety : understand it, then respond with self-compassion / by Charlotte Lieberman -- Working When You're Depressed : being productive can interrupt a negative spiral / by Alice Boyes -- Dealing with a Panic Attack : strategies for a scary situation / by Ruth White -- Section 3. Bringing Our Full Selves to Work: Being an'Only' at the Office : find strength in your uniqueness: an interview with Angela Neal-Barnett and Nilofer Merchant -- Supporting Women's Mental Health : what women themselves can do, and what leaders should / by Kelly Greenwood -- Prioritizing the Mental Health of People of Color : advice for individuals and decision makers / by Angela Neal-Barnett -- Section 4. Supporting Mental Health as a Manager: Reduce the Stigma of Mental Health at Work : five ways to drive an empathetic culture / by Diana O'Brien and Jen Fisher -- When Your Employee Discloses a Mental Health Condition : what to say, and what not to / by Amy Gallo -- Asking About Your Team's Mental Health Without Overstepping : talk about health holistically / by Deborah Grayson Riegel -- Managing an Employee with Depression : adjusting their hours, work scope, and deadlines can help / by Kristen Bell DeTienne, Jill M. Hooley, Cristian Larrocha, and Annsheri Reay -- Being Anxious When You're the Boss : you can inspire others when you're not OK / by Morra Aarons-Mele -- Section 5. Helping Colleagues Who Are Struggling: When You're Worried About a Colleague : figuring out what to say, and whether to say it / by Amy Gallo -- Noticing and Responding to Microaggressions : become more aware of the stressors your colleagues face / by Ella Washington -- Being a Mental Health Ally : give people the support you would want / by Katherine Ponte -- Section 6. Taking Action from the C-Suite: Living with Depression in the C- Suite : one executive's story of struggle and success: an interview with Paul Greenberg -- Offering the Mental Health Benefits BIPOC Employees Need : and ensuring they can easily access them / by Andrea Holman and Joe Grasso -- Forming an Employee Resource Group for Mental Health : build a community at work / by Jen Porter, Bernie Wong, and Kelly Greenwood -- Rewriting the Company's Mental Health Policy : don't tick boxes-truly help people / by Kelsey Raymond
Includes bibliographical references and index.
Keywords: Quality of work life -- Psychological aspects; Employees -- Mental health; Psychology, Pathological; Stigma (Social psychology).; Work -- Psychological aspects; Personnel management